Penerapan Word of Mouth dalam Membangun Kepercayaan Masyarakat dan Brand Image Universitas pada Keputusan Pemilihan UPBJJ-UT Ternate: The Application of Word of Mouth in Building Community Trust and University Brand Image on Selection Decision for UPBJJ-UT Ternate - Anfas Anfas; Ida Hidayanti; Mohbir Umasugi; Ibnu Sina Hi. Yusuf (Society, 2021)
This study examines the application of word of mouth to build community trust and university brand image on the community selection decision for UPBJJ-UT Ternate. The samples were obtained from eight regencies in North Maluku Province through a survey method aided with Smart PLS 3.8 analysis. In addition to the insignificant effect of university image on community selection decision, the findings indicated that (1) university image has a significant effect on word of mouth, (2) community trust has a significant effect on word of mouth, (3) community trust has a significant effect on selection decision, and (4) word of mouth has a significant effect on community selection decision.